Customers Perception about the Determinants of Service Quality of Foreign and Domestic Banks: An Empirical Study on Bangladesh (Journal of Business and Technology (Dhaka), 2012)
This paper investigates the determinants of perceived service quality among the customers of domestic and foreign banks in Dhaka, Bangladesh using a modified version of SERVQUAL model. It finds that in general the foreign banks provided marginally better measures in most of the dimensions than did the domestic banks. For domestic private banks reliability, communication, credibility, security, and tangibility are found to be significantly affecting the service quality. On the other hand, for foreign banks, reliability, credibility, and tangibility are the only significant factors affecting their service quality.Keywords: Determinants of Service quality; Banking industry; Bangladesh; SERVQUAL Model.DOI: http://dx.doi.org/10.3329/jbt.v6i1.9991  Journal of Technology (Dhaka) Vol. 6(1), January-June, 2011 1-14